1972
DOI: 10.1007/bf03005047
|View full text |Cite
|
Sign up to set email alerts
|

Awareness during general anaesthesia

Abstract: THE I'nOBLeM Or awareness during anaesthesia has existed since the introduction of the muscle relaxant technique. Any study of the problem must necessarily involve a study of the unconscious mind where such memories are recorded. It must also involve an understanding of some basic psychological mechanisms. The writer has attempted to correlate the published evidence, both clinical reports and research results, and evaluate this from his own experience in anaesthetics and clinical hypnotherapy. It is emphasized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Yet awareness and recall are only partly related because awareness may occur without remembrance (10). Also, studies reveal that a patient can recall an experience but can be unable to verbalize it (11,12). If we had measured awareness by evaluating recall, we would have reported an 8% incidence (3 of 36), which is similar to that reported in other studies (13)(14)(15).…”
Section: Discussionsupporting
confidence: 80%
“…Yet awareness and recall are only partly related because awareness may occur without remembrance (10). Also, studies reveal that a patient can recall an experience but can be unable to verbalize it (11,12). If we had measured awareness by evaluating recall, we would have reported an 8% incidence (3 of 36), which is similar to that reported in other studies (13)(14)(15).…”
Section: Discussionsupporting
confidence: 80%
“…They found that this was relatively constant at about 0.6 of the actual MAC for that agent. Scott (1972), in a review of reports of consciousness during anaesthesia, has described initial return of hearing, before discomfort or vision. Evidence of selective attention or awareness of "threatening" auditory input, as reported by Levinson (1965) on the basis of e.e.g.…”
Section: Initial Recovery From Anaesthesiamentioning
confidence: 99%
“…When using light anaesthesia in combination with muscle paralysis, it is possible for the patient to temporarily "surface" into a zone of partial or complete awareness (Scott 1972).11 Hearing appears to be the last sensation retained before loss of consciousness and is probably the first to return when consciousness is regained; hence this method of testing appeared justified to us. 94.6 per cent patients in Group I and 91.1 per cent in Group II could recall up to the moment of induction of anaesthesia, so that there was no significant retrograde amnesia in this series.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of Innovar appears to be one way of achieving this. Another method is the intermittent addition of inhalational adjuncts (Scott 1972). 11 Brice, Hetherington, and Utting ~~ found that the addition of 0.3 to 0.5 per cent halothane completely eliminated dreaming.…”
Section: Discussionmentioning
confidence: 99%